'Remittances are beautiful'? : gender implications of the new global remittances trend - Kunz, Rahel (2008)
Traces the emergence of the global remittances trend (GRT) and the way the link between migration, remittances and development is framed within it. Subjects the GRT to a critical gender perspective to explore its gendered foundations and its gender-specific implications.